Integrative taxonomy reveals six new species related to the Mediterranean corn stalk borer Sesamia nonagrioides (Lefèbvre) (Lepidoptera, Noctuidae, Sesamiina). (October 2015) - Kergoat, Gael J.; Toussaint, Emmanuel F. A.; Capdevielle‐Dulac, Claire; Clamens, Anne‐Laure; Ong'amo, George; Conlong, Desmond; van Den Berg, Johnnie; Cugala, Domingos; Pallangyo, Beatrice; Mubenga, Onesime; Chipabika, Gilson; Ndemah, Rose; et al.
<x xml:space="preserve">Abstract</x> Species in the stem borer noctuid subtribe Sesamiina are notoriously difficult to distinguish because most related species have homogeneous wing patterns and almost indistinguishable genitalia. The latter is potentially problematic because this group includes several important pest species that are usually baregly distinguishable from non‐pest species. In this study we focus on the Mediterranean corn stalk borer Sesamia nonagrioides (Lefèbvre), an important pest of maize with a wide area of distribution that covers most of Africa and extends to the south of Europe and western Asia. According to a recent study, this pest consists of three allopatric populations that were formerly considered as distinct species or subspecies. Here we rely on recent collections of 5470 specimens (sampled in 17 countries and 175 localities) that putatively belong to S. nonagrioides. Integrative taxonomy studies allowed us to unravel the existence of six new species that are closely related to S. nonagrioides and described in this paper. In contrast to S. nonagrioides these new species have more specific ecological preferences, as they are associated with a limited number of plant species and habitats. Dating and population genetic analyses carried out on 100 S. nonagrioides specimens also indicate a more complex population structure than previously thought for S. nonagrioides, which can probably be accounted for by late Cenozoic environmental changes. © 2015 The Linnean Society of London